44 Measuring an initiative's impact on inter-organisational collaborative capacity to deliver violence prevention activities. (9th June 2015) - Halverson, Julie; Czinner, Mary; Thomas, Lawrence; Johnson, Torre; Hernandez-Meier, Jennifer; Young, Staci
Abstract : Statement of purpose: The Medical College of Wisconsin Violence Prevention Initiative (VPI) engages partner teams that consist of multiple community agencies to effectively deliver violence prevention activities. Networking and other activities by teams aim to maximise sustainability by increasing both individual organisational capacity and the inter-organisational collaborative capacity (ICC) of partner teams. By describing the VPI's ongoing activities, experiences and results of evaluating ICC, we aim to provide information to initiatives seeking to measure capacity and overall impact. Methods/approach: ICC, including leadership, adaptive, management and operational dimensions, is assessed with an annual ICC Assessment (ICCA). Individual members complete an electronic ICCA, then the collective partnership team discusses their answers and reach consensus about their collective capacity. VPI evaluators develop and distribute final reports on team consensus scores to help teams identify capacity building goals. A team approach improves validity, reduces individual biases, and serves as a catalyst to engage in conversation about the team and needed/desired capacity building. Results: We describe how capacity building was incorporated into the VPI's goals, our process of measuring ICC of multiple agencies within a partner team and the ICCA tool used to measure and monitor ICC annually. We highlight how ICC has changed over time for one of our partner teams and how ICCA data has informed programmatic interventions and operational changes. Finally, we discuss how initiatives could measure ICC when selecting partners and setting capacity building goals. Conclusions: Utilising the ICCA for a collaborative, multi-agency approach to violence prevention was successful. Longitudinal data facilitates useful discussions regarding areas for improvement and goal setting and provide evaluation outcomes for individual organisations and teams and community-academic partnerships. Significance and contributions: Our experiences and 'lessons learned' may reinforce the utility of measuring ICC and provide strategies for incorporating ICC into goals, measurement plans and partner selection.